A retórica de Platão em cena: crítica filosófica e refutação no Fedro - Venuncia Emilia Coelho (2014)
The thesis analyses Plato's Phaedrus, taking as its guiding principle the philosophical reflection on rhetoric, understood as the dramatic staging of opposing speeches on love, in the first part of the dialogue, and as a reflection on persuasion, in the second. The main assumption is the confluence between form and content, that is, between the different rhetorical and discursive mechanisms used and the practice of refutation itself. On one hand, Socratic palinody is an example (paradeigma) of good rhetoric, since it provides definitions, it takes into account its specific auditorium, it is psychagogical, it uses dialectics and approaches another logos, aiming at refuting it. On the other hand, Lysias logos is presented as a mistaken discursive model, since it fails in providing definitions, it still relies on praising and condemning practices, not on the search for a definition of love, it is repetitive and does not establish a dialectical relation between parts and whole, that is, it is not organic. The thesis articulates these two perspectives by sustaining that, according to Plato´s dialectical rhetoric, good speeches are those which take up the task of refuting as well as of being themselves open to refutation. Refutation understood both as the characteristic of philosophical speeches and as the effect of psychagogy is the core that connects dramatic staging to argument. Finally, there is in the Phaedrus an indirect and ironical refutation that aims at Isocrates' rhetoric and that demonstrates the difference from which Plato builds his critique of established rhetoric.